Intraoperative Complications of High Volume Sutureless Cataract Surgery in Nepal: A Prospective Study - Limbo, B; Jha, HC (Kathmandu University Medical Journal, 2015)
BackgroundWith high backlog of cataract blindness in the developing countries sutureless high volume cataract surgery is preferred surgical technique.ObjectiveTo report the intraoperative complications of high volume sutureless cataract surgery at secondary level eye care centre of Nepal.MethodThis prospective study consisting 1087 eyes that underwent manual small incision cataract surgery from 2nd to 28th December 2007 at Shree Janaki Eye Hospital, Janakpur, Nepal and operated by a single eye surgeon. Preoperative and postoperative ocular findings together with intraoperative complications were carefully noted in every individual case. At post operative day one each patient was examined including uncorrected visual acuity and post operative complications which were subsequently recorded in Performa. Data were analysed using SPSS 11.5.ResultSixty-three eyes (5.8%) of 1087 eyes developed intraoperative complications. Out of 63 eyes that had intra operative complications, posterior capsular rupture were seen in 42 (3.9%), sclera corneal tunnel suturing in 12 eyes (1.1%), iridodialysis 5 eyes (0.5%) and Descemet stripping in 4 eyes (0.4%). 62.1% of patients attained uncorrected visual acuity 6/18 or better and in 91.7% of eyes, there were no post operative complications.ConclusionHigh volume suture less cataract surgery is safe surgery and should be continue in developing countries to achieve the goal of vision 2020, where there is huge backlog of cataract blindness.Kathmandu University Medical Journal Vol.12(3) 2014; 194-197